Treatment by ultrasound-guided local infiltration in adhesion-related abdominal pain and intractable hiccups: A case report. Issue 16 (April 2018) - Zhu, Dan; Gu, Zhi-Yong; Lin, Chia-Shiang; Nie, Fa-Chuan; Cui, Jian
Abstract: Rationale: Abdominal pain and hiccups secondary to intra-abdominal adhesion are surgical complications that are often treated by painkillers and secondary surgeries with an unsatisfactory therapeutic effect. This study presents a new treatment method that uses ultrasound-guided local infiltration in peritoneal and abdominal wall adhesions in patients with hiccups and abdominal pain. Patient concerns: A 62-year-old patient presented to our hospital with a history of intractable hiccups and abdominal pain for 30 years. Diagnoses: Her abdominal examination revealed a scar with an approximate length of 10 cm on the abdominal umbilical plane; pressing the right scar area could simultaneously induce abdominal pain and hiccups. Intraperitoneal computed tomography examination clearly demonstrated that the bowel had no obvious expansion. Ultrasonographic examination found that peritoneal motility below the normal peritoneal adhesion regions was significantly slower than in the normal regions. The diagnosis of chronic postoperative pain syndrome was clear. Interventions: The symptoms were significantly alleviated by a successful treatment with ultrasound-guided local infiltration in the peritoneal and abdominal wall scar adhesions. Outcomes: After 3 stages of hospitalization and 1 year of follow-up, the patient's abdominal wall pain was relieved by approximately 80% and hiccups were relieved by approximately 70%. Lessons: The above treatment is a useful option for managing abdominal adhesion and accompanying pain or hiccups resulting from abdominal surgery. This method could ease the psychological and economic burden of patients and improve their quality of life. Abstract : Supplemental Digital Content is available in the text